The miR156/SPL module regulates apple salt stress tolerance by activating MdWRKY100 expression - Ma, Yue; Xue, Hao; Zhang, Feng; Jiang, Qiu; Yang, Shuang; Yue, Pengtao; Wang, Feng; Zhang, Yuanyan; Li, Linguang; He, Ping; Zhang, Zhihong (Plant biotechnology journal, 2021)
Summary Salt stress dramatically impedes plant growth and development as well as crop yield. The apple production regions are reduced every year, because of the secondary salt damage by improper fertilization and irrigation. To expand the cultivation area of apple (Malus domestica) and select salt‐resistant varieties, the mechanism of salt tolerance in apple is necessary to be clarified. The miR156/SPL regulatory module plays key roles in embryogenesis, morphogenesis, life cycle stage transformation, flower formation and other processes. However, its roles in the mechanisms of salt tolerance are unknown. In order to elucidate the mechanism of 156/SPL regulating salt stress in apple, we performed RLM‐5’ RACE and stable genetic transformation technology to verify that both mdm‐MIR156a and MdSPL13 responded to salt stress in apple and that the latter was the target of the former. MIR156a overexpression weakened salt resistance in apple whereas MdSPL13 overexpression strengthened it. A total of 6094 differentially expressed genes relative to nontransgenic apple plants were found by RNA‐Seq analysis of MdSPL13OE. Further verification indicated that MdSPL13 targeted the MdWRKY100 gene promoter. Moreover, MdWRKY100 overexpression enhanced salt tolerance in apple. Our results revealed that the miR156/SPL module regulates salt tolerance by up‐regulating MdWRKY100 in apple. This study is the first to elucidate the mechanism underlying the miRNA network response to salt stress in apple and provides theoretical and empirical bases and genetic resources for the molecular breeding of salt tolerance in apple.